2019
DOI: 10.1136/bmj.l689
|View full text |Cite
|
Sign up to set email alerts
|

Benefits and harms of spinal manipulative therapy for the treatment of chronic low back pain: systematic review and meta-analysis of randomised controlled trials

Abstract: Objective To assess the benefits and harms of spinal manipulative therapy (SMT) for the treatment of chronic low back pain. Design Systematic review and meta-analysis of randomised controlled trials. Data sources Medline, PubMed, Embase, Cochrane Central Register of Controlled Trials (CENTRAL), CINAHL, Physiotherapy Evidence Database (PEDro), Index to Chiropractic Literature, and trial registries up to 4 May… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
195
1
15

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 247 publications
(217 citation statements)
references
References 77 publications
(542 reference statements)
6
195
1
15
Order By: Relevance
“…If two visits were separated by 3 weeks without visits (i.e. defined as two separate treatment periods in the statistical model), the analysis would then double count the last 3 weeks [5][6][7] in the first treatment period and the first 3 weeks [1][2][3] in the following treatment period. The mean number of visits for the whole cohort over 12 months was six visits, so the probability of double counting weeks without pain (as described above) was considered low, with little risk of distorting the results.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…If two visits were separated by 3 weeks without visits (i.e. defined as two separate treatment periods in the statistical model), the analysis would then double count the last 3 weeks [5][6][7] in the first treatment period and the first 3 weeks [1][2][3] in the following treatment period. The mean number of visits for the whole cohort over 12 months was six visits, so the probability of double counting weeks without pain (as described above) was considered low, with little risk of distorting the results.…”
Section: Methodsmentioning
confidence: 99%
“…A modest number of interventions have been shown to be effective in managing and treating recurrent and persistent LBP [3]. However, only exercise and exercise combined with education have been shown to reduce the number of new episodes [4][5][6][7].…”
Section: (Continued From Previous Page)mentioning
confidence: 99%
“…However, the evidence for both treatments is mixed. A recent systematic review suggested that spinal manipulation was no better than sham therapy for reducing pain or function at 6 and 12 months 22. A Cochrane review recommends against massage as an effective therapy for chronic LBP 23…”
Section: Second-line Care: Treatments To Consider Providingmentioning
confidence: 99%
“…mobilizations or high velocity low amplitude (HVLA) manipulations, are commonly used to treat musculoskeletal pain by chiropractors, osteopaths, and physical therapists [1]. Despite their common use and some clinical evidence supporting their efficacy [2][3][4], the mechanisms underlying these clinical effects are not really understood. The study of these potential mechanisms requires experimental research assessing body responses following the intervention.…”
Section: Introductionmentioning
confidence: 99%